TINJAUAN HUKUM ISLAM TERHADAP KONTROVERSI DAN DAMPAK LGBT BAGI PEMBANGUNAN KELUARGA DI INDONESIA - Samheri .; Emilia Angraini (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2023)
This paper examines the controversy of LGBT on family development in Indonesia. LGBT is a group of lesbian, gay, bisexual and transgender. Recently it was hotly discussed because the British Embassywhich raised the rainbow flag as a symbol of LGBT at its headquarters in Jakarta. It attracted public attention. This paper is library research. The results of this research analysis show that behavior that deviates from LGBT violates rules and human nature and has a negative impact on the development of families and the nation in general. The negative impact are in the form of health, education, security and social. Thus if it is left too long then this wrong thing will become a natural thing. In fact, from the point of view of religious and humanitarian law. This contradicts both. Even though these LGBT perpetrators argue based on human right principles, all this cannot prove the truth of their deviant behavior because human rights in Indonesia must be in harmony with the philosophy of the state based on Pancasila in which Pancasila plates Believe in One Almighty God as the main foundation for trenght of a notion. The majority of this notion adheres to Islamic Law and adheres to Pancasila.